Glycyrrhetinic Acid Antagonizes Pressure-Induced Venous Remodeling in Mice - Kuk, Hanna; Arnold, Caroline; Wagner, Andreas H.; Hecker, Markus; Sticht, Carsten; Korff, Thomas (Frontiers in Physiology, 2018)
Development of spider veins is caused by the remodeling of veins located in the upper dermis and promoted by risk factors such as obesity or pregnancy that chronically increase venous pressure. We have repeatedly shown that the pressure-induced increase in biomechanical wall stress is sufficient to evoke the formation of enlarged corkscrew-like superficial veins in mice. Subsequent experimental approaches revealed that interference with endothelial- and/or smooth muscle cell activation counteracts this remodeling process. Here, we investigate whether the herbal agent glycyrrhetinic acid (GA) is a suitable candidate for that purpose given its anti-proliferative as well as anti-oxidative properties. While basic abilities of cultured venous smooth muscle cells (SMCs) such as migration and proliferation were not influenced by GA, it inhibited proliferation but not angiogenic sprouting of human venous endothelial cells (ECs). Further analyses of biomechanically stimulated ECs revealed that GA inhibits the DNA binding capacity of the mechanosensitive transcription factor activator protein-1 (AP-1) which, however, had only a minor impact on the endothelial transcriptome. Nevertheless, by decreasing gelatinase activity in ECs or mouse veins exposed to biomechanical stress, GA diminished a crucial cellular response in the context of venous remodeling. In line with the observed inhibitory effects, local transdermal application of GA attenuated pressure-mediated enlargement of veins in the mouse auricle. In summary, our data identifies GA as an inhibitor of EC proliferation, gelatinase activity and venous remodeling. It may thus have the capacity to attenuate spider vein formation and remodeling in humans.